1999
DOI: 10.1111/0022-1082.00184
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Theory of Underreaction, Momentum Trading, and Overreaction in Asset Markets

Abstract: We model a market populated by two groups of boundedly rational agents: "newswatchers" and "momentum traders." Each newswatcher observes some private information, but fails to extract other newswatchers' information from prices. If information diffuses gradually across the population, prices underreact in the short run. The underreaction means that the momentum traders can profit by trendchasing. However, if they can only implement simple~i.e., univariate! strategies, their attempts at arbitrage must inevitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

136
1,221
8
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,360 publications
(1,456 citation statements)
references
References 64 publications
136
1,221
8
12
Order By: Relevance
“…Jegadeesh and Titman (1993) demonstrated that stocks that produced low return in the previous year tend to achieve low returns in the following months, whereas stocks that produced high returns in the previous months tend to accomplish high returns in the following months. Other studies show an inverse relation between past and following returns (Daniel, Hirshleifer, & Subrahmanyam, 1998;Hong & Stein, 1999). Still, there is evidence of a negative relation between return rate and investment (Fairfield, Whisenant, & Yohn, 2003;Titman, Wei, & Xie, 2004); high accruals and following returns (Sloan, 1996), and; equity issuance and return rate (Daniel & Titman, 2006;Pontiff & Woodgate, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Jegadeesh and Titman (1993) demonstrated that stocks that produced low return in the previous year tend to achieve low returns in the following months, whereas stocks that produced high returns in the previous months tend to accomplish high returns in the following months. Other studies show an inverse relation between past and following returns (Daniel, Hirshleifer, & Subrahmanyam, 1998;Hong & Stein, 1999). Still, there is evidence of a negative relation between return rate and investment (Fairfield, Whisenant, & Yohn, 2003;Titman, Wei, & Xie, 2004); high accruals and following returns (Sloan, 1996), and; equity issuance and return rate (Daniel & Titman, 2006;Pontiff & Woodgate, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…In the model by Hong and Stein (1999), there are two types of traders exhibiting bounded rationality. So-called newswatchers establish their beliefs on the fundamental value of the asset solely based on the private information derived from the analysis of the asset under review, and they disregard the information from market prices that is otherwise observable.…”
Section: Studiesmentioning
confidence: 99%
“…In this context of psychological analysis, Shiller (1981) attributes the financial bias to irrationality and postulates that stock prices vary too much relatively to news about future dividends. Similarly, Hong and Stein (1999) studied the overreaction by modeling the operators" interaction who naively follow trend of prices and other operators.…”
Section: The Irrationality Of Financial Analystsmentioning
confidence: 99%
“…This intensifies the opinion differences which does deviate the quotes away from their fundamentals. Hong and Stein (1999), Barberis and Thaler (2002) consider that excessive confidence on private information leads operators to revise their beliefs too little in response to subsequent public news. Kent and Titman (2000) define excessive confidence as if the accuracy of the error component of private information signal is larger than it really is, but operators do remain Bayesian.…”
Section: Excessive Confidence and Operators' Irrationalitymentioning
confidence: 99%